2021
DOI: 10.1371/journal.pone.0258644
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multi-assay algorithms for identifying individuals with recent HIV infection: HPTN 071 (PopART)

Abstract: Background Assays and multi-assay algorithms (MAAs) have been developed for population-level cross-sectional HIV incidence estimation. These algorithms use a combination of serologic and/or non-serologic biomarkers to assess the duration of infection. We evaluated the performance of four MAAs for individual-level recency assessments. Methods Samples were obtained from 220 seroconverters (infected <1 year) and 4,396 non-seroconverters (infected >1 year) enrolled in an HIV prevention trial (HPTN 071 [Pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…Only 24 (11.0%) of the seroconverters were classified as recently infected by all three MAAs. This is consistent with a prior report that showed that different MAAs identify different subsets of seroconverters as recently infected [ 7 ]; the different classification of individual seroconverters as recently infected was not solely due to exclusions for viral load. In this study, 80 of the seroconverters were classified as recent by the LAg + BR MAA.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Only 24 (11.0%) of the seroconverters were classified as recently infected by all three MAAs. This is consistent with a prior report that showed that different MAAs identify different subsets of seroconverters as recently infected [ 7 ]; the different classification of individual seroconverters as recently infected was not solely due to exclusions for viral load. In this study, 80 of the seroconverters were classified as recent by the LAg + BR MAA.…”
Section: Resultssupporting
confidence: 92%
“…Multi-assay algorithms (MAAs) have been developed for estimating population-level HIV incidence using samples collected in cross-sectional surveys [ 1 3 ]. These algorithms have also been used to identify individuals with recent HIV infection [ 4 7 ]. The most widely used MAA includes the Limiting Antigen Avidity assay (LAg-Avidity assay) and HIV viral load (LAg + VL MAA) [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations